BiciZen: Lessons in the Development of a Crowdsourcing Mobile App to Make Cities More Bikeable - Jordi Honey-Rosés; Luca Liebscht; Paulo Batista; Boualem Benatallah; Mark Brussel; Johannes Flacke; Jouni Häkli; Kirsi Pauliina Kallio; Theo Lynn; Miki Mäkelä; Lourenço Melo; Gemma Simón-i-Mas; et al. (Journal of Participatory Research Methods)
Improving bikeability is an urban policy goal that cities are pursuing to reduce their transport-related carbon emissions. To support this goal, this paper introduces BiciZen: a collaborative platform that aims to make cities and regions more bikeable. We describe the lessons learned from the development of this citizen science project. BiciZen is a mobile phone app that allows users to crowdsource information about their cycling experiences and suggest improvements to cycling infrastructure as well as report positive cycling experiences. BiciZen is open to concerned cyclists, city planners and researchers who wish to document and study cycling phenomena, including patterns of bicycle flows or participation in cycling events. The process of developing BiciZen highlights critical trade-offs pertaining to functionality, speed, cost, and flexibility. We found that when deciding what to include in the platform, the interests of researchers, users and city leaders did not necessarily align. We learned that feedback processes are valuable but highly resource intensive. Less than a year after the launch of BiciZen, we find that uptake has been highest in low-cycling contexts and driven mostly by a small number of super-users. The data collected on the BiciZen platform will provide a historical record of cycling incidents, events, and commentary that can be consulted by all stakeholders, and help advance co-creation and citizen science in the realm of active travel and bicycle mobility.